Re-collection and identity of Ooencyrtus californicus (Hymenoptera: Encyrtidae), and its new synonym, Ooencyrtus lucidus - Triapitsyn, Serguei V.; Rugman-Jones, Paul F.; Perring, Thomas M. (Zootaxa, 2021)
Girault (1917) very briefly described and diagnosed the encyrtid wasp species Ooencyrtus californicus Girault (Hymenoptera: Encyrtidae) with the following limited data (p. 22): “Sacramento, California, from bug eggs on Pinus sabiniana, September”. The first author examined its two syntypes, poorly mounted on a slide, of which only parts of the four antennae and a slightly damaged fore wing remain (Triapitsyn et al. 2020). They concluded that this species was better considered a nomen dubium until fresh specimens could be collected from the same host plant in or near the type locality. In July 2019, an effort was made to re-collect O. californicus from foothill (or gray) pine, Pinus sabiniana (Pinaceae), in the Oakhurst area of Madera County, California, USA, where this pine is abundant, but no specimens were captured. At the same time, a very similar insect was collected from sentinel eggs of the invasive stink bug Bagrada hilaris (Burmeister) in Riverside, California. This insect was cultured in the laboratory as part of a B. hilaris biological control program. Due to the poor preservation of the type specimens and in the absence of genetic evidence, it was impossible to positively and properly attribute specimens of this newly collected parasitoid to O. californicus. Therefore, to provide a much needed scientific name for this native egg parasitoid, it was described as Ooencyrtus lucidus Triapitsyn & Ganjisaffar in Triapitsyn et al. (2020). The two nominal species were separated based on minor differences in the proportions of the scape, pedicel, and first funicular segment of the female antenna (Triapitsyn et al. 2020). John S. Noyes, world expert on Encyrtidae and one of the reviewers of Triapitsyn et al. (2020), disagreed with the erection of O. lucidus as a new taxon based on the morphological similarities of the female antenna with that of O. californicus, so the description was published with the understanding that the two might be conspecific. But to settle this one way or another new specimens of O. californicus had to be collected to allow morphological and molecular analyses.